2020
DOI: 10.1007/s40195-020-01109-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed Magnetic Field on the Residual Stress of Rolled Magnium Alloy AZ31 Sheet

Abstract: A novel method of pulsed magnetic field (PMF) treatment was developed to eliminate the residual stress of rolled magnesium alloy AZ31 sheet in this study. The effect of PMF on residual stress of rolled AZ31 sheet was investigated and its mechanism was analyzed. The experimental results revealed that the pulse frequency had a significant impact on residual stress. After 10.0 Hz PMF treatment, the average and maximum reduction rates of residual stress along the rolled direction were 26.6% and 30.3%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…9. Similar phenomena have been observed in other materials, including the M50 steel [53], AZ31 magnesium alloy [54], Al matrix composites [55], etc. It is noteworthy that the reverse effect is more commonly reported with a higher magnetic intensity in the research.…”
Section: Comprehensive Effect Of Pmt On Microstructuresupporting
confidence: 84%
“…9. Similar phenomena have been observed in other materials, including the M50 steel [53], AZ31 magnesium alloy [54], Al matrix composites [55], etc. It is noteworthy that the reverse effect is more commonly reported with a higher magnetic intensity in the research.…”
Section: Comprehensive Effect Of Pmt On Microstructuresupporting
confidence: 84%
“…According to the above theory, it can be inferred that the dislocation in the aluminium bronze alloy becomes more easily depinned and moved under the influence of the original stress field, due to the change in the electronic energy state at the pinned place during the pulsed magnetic field treatment. On the one hand, the dislocation movement reduced the stress concentration caused by the dislocation pile-up, relaxed the original stress, and reduced the residual stress of the alloy, as verified by the significant reduction in residual stress in the magnetic field treatment of aluminium alloy [ 7 ], nickel–aluminium bronze [ 9 ], EN8 special steel [ 10 ], titanium alloy [ 26 ], and magnesium alloy [ 27 ]. On the other hand, the dislocation movement somewhat altered the grain boundary angle, resulting in an apparent reduction in LAGBs and the disappearance of twin boundaries, which lowered the system energy.…”
Section: Discussionmentioning
confidence: 99%
“…When aluminum alloy [21,30], aluminum bronze alloy [33], EN8 steel [34], titanium alloy [37], and magnesium alloy [52,53] were treated with magnetic field, the residual stress of the alloy was obviously reduced. Further analysis showed that the residual tensile stress of alloy decreased gradually to the residual compressive stress under the magnetic field, while the sample initially showed residual compressive stress increased gradually under the magnetic field.…”
Section: Magnetic Field Changes Residual Stress Distributionmentioning
confidence: 99%